2016
DOI: 10.1155/2016/8653132
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmunology of Huntington’s Disease: Revisiting Evidence from Human Studies

Abstract: Huntington's disease (HD) is a neurodegenerative disorder characterized by selective loss of neurons in the striatum and cortex, which leads to progressive motor dysfunction, cognitive decline, and psychiatric disorders. Although the cause of HD is well described—HD is a genetic disorder caused by a trinucleotide (CAG) repeat expansion in the gene encoding for huntingtin (HTT) on chromosome 4p16.3—the ultimate cause of neuronal death is still uncertain. Apart from impairment in systems for handling abnormal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 63 publications
2
61
0
1
Order By: Relevance
“…HD patients show a positive pro-inflammatory profile (Figure 1) correlated with the disease's progression, including increases of IL-1β, IL-6, and TNF-α in the striatum, cerebral spinal fluid and plasma that were also confirmed in mouse models (Rocha et al, 2016). Central immune activation in HD subjects was confirmed using positron emission tomography (PET) and in pre-symptomatic HD-gene carriers (Rocha et al, 2016). Even though pharmacologic immune modulation using the XPro1595 TNF-α inhibitor has shown neuroprotection against the cytokine-induced neurotoxicity in primary R6/2 neurons and human neurons derived from iPSCs of HD patients (Hsiao et al, 2014), the information available is contradictory based on one report describing that neuroinflammation seems a consequence rather than a cause of neurodegeneration in late HD (Vinther-Jensen et al, 2016).…”
Section: Active Immunity In Huntington's Disease (Hd)mentioning
confidence: 72%
See 1 more Smart Citation
“…HD patients show a positive pro-inflammatory profile (Figure 1) correlated with the disease's progression, including increases of IL-1β, IL-6, and TNF-α in the striatum, cerebral spinal fluid and plasma that were also confirmed in mouse models (Rocha et al, 2016). Central immune activation in HD subjects was confirmed using positron emission tomography (PET) and in pre-symptomatic HD-gene carriers (Rocha et al, 2016). Even though pharmacologic immune modulation using the XPro1595 TNF-α inhibitor has shown neuroprotection against the cytokine-induced neurotoxicity in primary R6/2 neurons and human neurons derived from iPSCs of HD patients (Hsiao et al, 2014), the information available is contradictory based on one report describing that neuroinflammation seems a consequence rather than a cause of neurodegeneration in late HD (Vinther-Jensen et al, 2016).…”
Section: Active Immunity In Huntington's Disease (Hd)mentioning
confidence: 72%
“…Huntington's disease is an autosomal-dominant neurodegenerative disease caused by a CAG trinucleotide repeat expansion that gives place to a polyglutamine region in the huntingtin protein (HTT). HD patients show a positive pro-inflammatory profile (Figure 1) correlated with the disease's progression, including increases of IL-1β, IL-6, and TNF-α in the striatum, cerebral spinal fluid and plasma that were also confirmed in mouse models (Rocha et al, 2016). Central immune activation in HD subjects was confirmed using positron emission tomography (PET) and in pre-symptomatic HD-gene carriers (Rocha et al, 2016).…”
Section: Active Immunity In Huntington's Disease (Hd)mentioning
confidence: 88%
“…MPF can also be affected by inflammation (Henkelman, Stanisz, & Graham, 2001) and in manifest HD it is likely that inflammation goes hand in hand with myelin breakdown (Rocha et al, 2016). However, a recent CSF biomarker study found no evidence of neuro-inflammation in early-manifest HD (Vinther-Jensen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inflammation has now been shown to be important in many chronic neurodegenerative disorders of the brain such as Alzheimer's disease (AD) and Parkinson's disease as well as HD . The evidence for a key role of inflammation to HD comes from studies looking at microglial activation on imaging and pathologically as well as peripheral cytokine profiles, which can be found early on in the disease.…”
mentioning
confidence: 99%
“…[19][20][21] In addition, inflammation has now been shown to be important in many chronic neurodegenerative disorders of the brain such as Alzheimer's disease (AD) 22 and Parkinson's disease 23 as well as HD. 24 The evidence for a key role of inflammation to HD comes from studies looking at microglial activation on imaging and pathologically 25 as well as peripheral cytokine profiles, 26 which can be found early on in the disease. Inflammation-related genetic modifiers have also been shown to influence the risk of developing neurodegenerative disorders such as sporadic AD, and this includes the triggering receptor expressed on myeloid cells 2 (TREM2) [27][28][29][30][31][32][33] and toll-like receptor 4 (TLR4).…”
mentioning
confidence: 99%